2010
DOI: 10.1536/ihj.51.170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hypoxia at Moderate Altitude on Stroke Volume and Cardiac Output During Exercise

Abstract: SummaryIt has been unclear how acute hypoxia at moderate altitude affects stroke volume (SV), an index of cardiac function, during exercise. The present study was conducted to reveal whether acute normobaric hypoxia might alter SV during exercise.Nine healthy male subjects performed maximal exercise testing under normobaric normoxic, and normobaric hypoxic conditions (O 2 : 14.4%) in a randomized order. A novel thoracic impedance method was used to continuously measure SV and cardiac output (CO) during exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 36 publications
0
32
2
Order By: Relevance
“…11,12,16) Two sets of electrodes (one transmitting electrode and one sensing electrode) were applied above the supraclavicular fossa at the left base of the neck and along the xiphoid, respectively. Another set of two electrodes was used to monitor ECG (V1/V6 position).…”
Section: )mentioning
confidence: 99%
“…11,12,16) Two sets of electrodes (one transmitting electrode and one sensing electrode) were applied above the supraclavicular fossa at the left base of the neck and along the xiphoid, respectively. Another set of two electrodes was used to monitor ECG (V1/V6 position).…”
Section: )mentioning
confidence: 99%
“…In a systematic analysis of the literature cited in PubMed (see APPENDIX A; search terms and inclusion/exclusion criteria are detailed in Table A1), including at least eight participants, we found five randomized-controlled trials providing data on the effects of hypobaric hypoxia, normobaric hypoxic gas mixtures, or altitude exposure on exercise capacity quantified by W max or V O 2 (Tables A1 and A2). Two of the studies were crossover trials in hypobaric chambers (altitude equivalent of 3,800 m and up to 2,286 m) (60,71), where subjects were blinded to the chamber pressure, a third was a field study in Indian soldiers (58), which were randomized to exercise near sea level or after 4 wk of acclimatization to 4,560 m, and two used normobaric hypoxia (9,16). All studies showed a decreased exercise performance in V O 2max under hypoxia compared with ambient air near sea level.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are doubts to SV during MLE in moderately trained subjects, with an SV plateau at submaximal-exercise intensity [23]. We found only one study that showed an increase in SV in nonathletic subjects [24]. This evidence indicates that a high level of physical fitness may be required to obtain increased SV during MLE.…”
Section: Discussionmentioning
confidence: 92%